Biocompatibility of gold nanoparticles and their endocytotic fate inside the cellular compartment: a microscopic overview - Shukla, Ravi; Bansal, Vipul; Chaudhary, Manakshi; Basu, Atanu; Bhonde, Ramesh R.; Sastry, Murali (Langmuir, 2005)
Macrophages are one of the principal immune effector cells that play essential roles as secretory, phagocytic, and antigen-presenting cells in the immune system. In this study, we address the issue of cytotoxicity and immunogenic effects of gold nanoparticles on RAW264.7 macrophage cells. The cytotoxicity of gold nanoparticles has been correlated with a detailed study of their endocytotic uptake using various microscopy tools such as atomic force microscopy (AFM), confocal-laser-scanning microscopy (CFLSM), and transmission electron microscopy (TEM). Our findings suggest that Au(0) nanoparticles are not cytotoxic, reduce the production of reactive oxygen and nitrite species, and do not elicit secretion of proinflammatory cytokines TNF-alpha and IL1-, making them suitable candidates for nanomedicine. AFM measurements suggest that gold nanoparticles are internalized inside the cell via a mechanism involving pinocytosis, while CFLSM and TEM studies indicate their internalization in lysosomal bodies arranged in perinuclear fashion. Our studies thus underline the noncytotoxic, nonimmunogenic, and biocompatible properties ofgold nanoparticles with the potential for application in nanoimmunology, nanomedicine, and nanobiotechnology.

Double encapsulation of liquid active compounds using nanoclay reinforced polyurea microcapsules - Aher, Yogeshwar P.; Torris, Arun; Adhikari, Benu; Shukla, Ravi; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2023)
In recent years, there has been growing interest in the double encapsulation of drugs, agrochemicals, and fragrances, aiming to achieve the highest encapsulation efficiency and preserve the activity of the encapsulated core over an extended duration. However, when active ingredients in liquid form are double encapsulated, preventing the rupture of primary microcapsules during the second encapsulation process and the leakage of the encapsulated core are major challenges. This report describes a method that utilizes polyurea and starch for successful double encapsulation of dimethyl phthalate (DMP), a liquid insect-repellent, as a model active component. We demonstrate that the incorporation of 3 wt% montmorillonite (MMT) nanoclay strengthens the polyurea wall of the primary microcapsule and prevents its rupture during double encapsulation with starch. This process facilitates the uniform distribution of polyurea microcapsules within the starch matrix and significantly improves the mechanical integrity of the nanocomposite microcapsules embedded in starch. The double-encapsulated system developed in this study significantly reduces the release rate of encapsulated DMP.
Keywords: Controlled release; Double encapsulation; Microcapsules; Microencapsulation; Nanocomposites; Starch matrix

Double-encapsulated controlled release system for the staged delivery of a growth stimulant and herbicide - Aher, Yogeshwar P.; Adhikari, Benu; Shukla, Ravi; Marimuthu, S.; Shanmuganathan, Kadhiravan (ACS Agricultural Science & Technology, 2025)
Weed control remains a critical challenge in agriculture, especially with parasitic weeds such as Orobanche spp., Striga spp., and Cuscuta spp., which significantly reduce crop yield. Although herbicides are effective against common weeds, they are less effective against parasitic weeds due to their unique germination mechanisms and close association with host plants. Growth regulators can stimulate the germination of parasitic weeds (suicidal germination) in the absence of host plants, providing a potential opportunity for controlling parasitic weeds, especially Striga sps. We report here a double-encapsulated staged delivery system, wherein herbicide (atrazine) is encapsulated in the inner polyurea shell and a growth stimulant (Gibberellic acid, GA3) in the outer alginate matrix. In vitro release study conducted in an aqueous medium showed that the time required for 50% release of atrazine from this double-encapsulated system is 96 h against 3 h for GA3. The quick release of GA3, followed by a slow and sustained release of atrazine, is expected to first induce the germination of parasitic weed seeds using GA3 and subsequently exterminate them upon exposure to atrazine. Interpretation of release data using the Weibull model led to the conclusion that the release of atrazine and GA3 is primarily governed by Fickian diffusion. Soil breakthrough profile shows that double encapsulation of atrazine helps to control the overleaching of atrazine into the soil.